The role of career adaptability resources in dual career pathways: A person-oriented longitudinal study across elite sports upper secondary school - Ojala, J.; Nikander, A.; Aunola, K.; De Palo, J.; Ryba, T. V. (Psychology of Sport and Exercise, 2023)
Objectives Obtaining education is an important milestone in athletes` preparation for their professional career after sport. Literature indicates that combining school and sport is not an easy task for many aspiring youth athletes. It has been proposed that career adaptability, which refers to psychosocial resources enabling individuals to solve complex occupational transitions, present and anticipated vocational development tasks, and career related challenges could be a relevant concept for applied work with student-athletes. In this study, we examined whether there are distinct developmental profiles of career adaptability among adolescent athletes across the upper secondary school years. We also investigated the associations between career adaptability and sport withdrawal and academic achievement.